Hydrophilicity and Water Contact Angle on Methylammonium Lead Iodide. Issue 3 (7th December 2018) - Caddeo, Claudia; Marongiu, Daniela; Meloni, Simone; Filippetti, Alessio; Quochi, Francesco; Saba, Michele; Mattoni, Alessandro
Abstract: Surface properties are often assessed with measurements of the contact angle of a water drop. The process is however flawed for the very important class of hybrid perovskite materials, extensively employed in solar cells and optoelectronics research, because they are water soluble and their surface degrades during contact angle measurements. While hybrid perovskites are considered to be highly hydrophilic, a contact angle with water of 83° can be measured, as if they were almost hydrophobic. By combining experiments and simulations, the actual value is explained as the result of the interaction of water with degraded superficial layers that form over sub‐millisecond time scale at the water/perovskite interface. The models are validated against contact angle measurements for water on a variety of substrates, and are referenced to with the Young–Dupré relation between liquid–solid adhesion and contact angle. Present work reconciles the hydrophilic nature of methylammonium lead iodide with the apparent hydrophobic behavior in contact angle measurements, proposing a methodology for the study of contact angle on evolving substrates. Abstract : Model potential molecular dynamics explains the large water contact angle observed on hydrophilic methylammonium lead iodide. Liquid water degrades the methylammonium lead iodide surface with the formation of superficial hydrophobic lead iodide layers already in the first milliseconds after contact. Present study paves the way to the characterization of degrading perovskites by water contact angle measurements.